2013
DOI: 10.4322/polimeros.2013.053
|View full text |Cite
|
Sign up to set email alerts
|

Rugosidade e Microscopia de Força Atômica de Resinas Compostas Submetidas a Diferentes Métodos de Polimento

Abstract: Resumo: Este trabalho avaliou a rugosidade e a topografia de superfície de resinas compostas submetidas a diferentes métodos de polimento. Foram utilizadas 5 resinas (Filtek Z350, Master Fill, Vênus, Charisma e Durafill VS) e confeccionou-se 90 corpos de prova distribuídos em 6 grupos (n:15): SP: sem polimento; TB: ponta de borracha abrasiva; DL: disco de lixa em três granulações; FP: disco de feltro com pasta diamantada; ECS: escova de carbeto de silício; PS: ponta de silicone abrasiva. Após os polimentos, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Thus, C and PD groups of both composites exposed values above this threshold, as well as EN of BF. Authors such as Martins Alves et al 15 and Sahbz et al 20 expose that, when values of approximately 0.4 µm are exceeded, roughness can be clinically observed by the patient, so this could be verified in C groups of both composites, as well as in PF of BF.…”
Section: Resultand Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, C and PD groups of both composites exposed values above this threshold, as well as EN of BF. Authors such as Martins Alves et al 15 and Sahbz et al 20 expose that, when values of approximately 0.4 µm are exceeded, roughness can be clinically observed by the patient, so this could be verified in C groups of both composites, as well as in PF of BF.…”
Section: Resultand Discussionmentioning
confidence: 97%
“…For PD group (felt disc + diamond paste), it is noted that this system considerably reduced the surface roughness left by the diamond tip, possibly because it has high hardness micronized abrasive diamond grains, wearing the particles that were exposed irregularly 15 . Just as in the current research, the findings of Martins Alves et al 15 and Bittencourt et al 23 also confirmed the influence of this polishing mechanism on the roughness of compound resins, visualizing a decrease in Ra values when used on rough surfaces. In contrast, Costa et al 2 suggest that the use of diamond paste in composite resins may be of value when used later on for instruments with aluminum oxide in the composition, in the case of this study, present in Sof-Lex and Enhance.…”
Section: Resultand Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main characteristics of the 34 selected in vitro studies are presented in the supplemental material (Table S2) [1, 16–48]. All selected studies were conducted on resin composite specimens and pre‐roughened with diamond burs.…”
Section: Resultsmentioning
confidence: 99%